2002
DOI: 10.1038/sj.cr.7290139
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellular adhesion molecule expression in murine oocytes, peri-implantation and post-implantation embryos

Abstract: Expression of the adhesion molecules, ICAM-1, VCAM-1, NCAM, CD44, CD49d (VLA-4, α chain), and CD11a (LFA-1, α chain) on mouse oocytes, and pre-and peri-implantation stage embryos was examined by quantitative indirect immunofluorescence microscopy. ICAM-1 was most strongly expressed at the oocyte stage, gradually declining almost to undetectable levels by the expanded blastocyst stage. NCAM, also expressed maximally on the oocyte, declined to undetectable levels beyond the morula stage. On the other hand, CD44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In mammalian embryo development, a blastocyst is formed followed by a series of events in vivo, such as hatching from the zona pellucida, implantation and embryonic outgrowth (Lu et al 2002). Here in this study, embryo outgrowth was defined according to the criteria that outgrowth distances reach half of the embryo's diameter with at least five giant trophoblast cells observed at the edge of outgrowing trophoblast cells (Spindle & Pedersen 1973).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian embryo development, a blastocyst is formed followed by a series of events in vivo, such as hatching from the zona pellucida, implantation and embryonic outgrowth (Lu et al 2002). Here in this study, embryo outgrowth was defined according to the criteria that outgrowth distances reach half of the embryo's diameter with at least five giant trophoblast cells observed at the edge of outgrowing trophoblast cells (Spindle & Pedersen 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Resumption of meiosis in MII oocytes is controlled by maturation promoting factor protein that acts to regulate MAP kinase (MAPK) via activation of an oocyte exclusive kinase. The active c-mos kinase promotes MAP kinase (MEK) phosphorylation of MAPK and its activation (Lu et al 2002, Josefsberg et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggest that ROCK1 and ROCK2 may play distinct, and sometimes opposing, roles in such cells (Yoneda et al 2005(Yoneda et al , 2007. In mammals, several reports have shown that the compaction process, involving cytoskeletal rearrangement and development of intercellular adhesion, is critical for the development of viable embryos (Lu et al 2002, Kawagishi et al 2004. Rho family signaling is considered to be the principal mechanism whereby oocyte maturation and embryo development are controlled.…”
Section: Introductionmentioning
confidence: 99%